Aspek Kelayakan Usaha dan Strategi Pemasaran Pallet dengan ISPM#15 pada PT XYZ di Palembang - Lanny Syamsir; Musa Hubeis; Nora H. Pandjaitan (Institut Pertanian Bogor, 2009)
Packing made from wood is one of the choices in transporting commodity to protect a product effectively. In 2002, FAO determined the International Standard for Phytosanitary Measure (ISPM) which is the standard that arranges the quarantine of plants for wood packing used in international trade. In Indonesia ISPM is done by Badan Karantina Pertanian (Barantan). The objectives of this study are to evaluate the feasibility of its Palembang branch, to arrange a suitable marketing strategy and to asses its possible development to become a single entity firm (separate from the main office). The analysis of the study in Palembang showed that this branch office is feasible, with an NPV positive of Rp 928,99 million and an IRR of 26,93% (higher than the capital interest of 14%), and a PBP for 3 year 1 month PBP (shorter than the 4-year credit term). The IE matrix used shows that the company is in the first matrix position; therefore, the strategy of growth is used. From the SWOT analysis there are 4 alternative strategies such as S-O, W-O, S-T and W-T. These strategies are formulated into the marketing strategy that can be applied based on mixed marketing: (1) product strategy: maintenance of product quality and innovation in the design of production system, to accelerate the production process and to improve productivity using skilled labor; (2) the price strategy: reducing price based on BEP calculation and applying cost efficiency; (3) the location strategy: closer to market and raw material resources and maintaining relationship with distribution channels; (4) the promotion strategy: introducing the company to potential customers.